Analysis of propeller bearing loads by CFD. Part I: Straight ahead and steady turning maneuvers. (15th January 2017) - Dubbioso, Giulio; Muscari, Roberto; Ortolani, Fabrizio; Di Mascio, Andrea
Abstract: Marine propellers in behind-hull conditions develop, in addition to thrust and torque, in-plane loads that are strictly related to fatigue stress of the propulsive shaft bearings, hull-induced vibrations and the dynamic response of the ship while maneuvering or experiencing wave induced motions. An in-depth understanding of their nature as well as their quantification in typical design and off-design operative scenario is fundamental for improving ship design criteria. This issue is tackled in the present work by means of URANS simulations and simplified propeller theories to assess the correlation between inflow conditions and propeller loads. In particular, the analysis is carried out for the same twin screw model recently considered in free running maneuvering model tests (Ortolani et al., 2015a, 2015b) and further aims to provide a complementary and deeper insight to the outcome of these experiments. The first part of the study is focused on the straight ahead motion and the steady turning maneuvers with rudder deflections of 15°, 25° and 35° and Froude number equal to 0.26. Highlights: Analysis of propeller loads during turning circles maneuvres by CFD. Use of simplified propeller models based on momentum theory and BEMT. Phenomenological inspection by cross-correlation between the loads and wake. Differences of the features on the two propellers are stressed. Complementary perspective to the experimental analysis (Ortolani et al., 2015a, 2015b ).